Responsabilidade social no âmbito da Bolsa de Valores de São Paulo - Souza, Wagner Roberto Roxo de Pádua (2006)
This is a descriptive-analytical study of corporate social responsibility, a phenomenon that leads companies to this relatively new field of corporate social investments. This work begun with the following fundamental question: why companies should assume social responsibilities? A first hypothesis was that companies make social investments to build or improve its reputation on the market, considered as a competitive advantage. Alternatively, a second hypothesis assumed the idea that corporate social responsibility lies on moral grounds: companies struggle to build a better society because this is the morally correct way they are expected to be. It was researched the Brazil Stock Exchange (BOVESPA) that recently created and launched its Social Stock Exchange, a new alternative now available for Non-governmental organizations (NGOs) to raise funds. Besides, the social exchange gives visibility and credibility to unknown NGOs. Thirty two interviews were carried out with leaders of the NGOs which once had or still had social projects listed in the Social Stock Exchange. We come to the conclusion that the NGOs´ leaders realized BOVESPA´s intention of causing a positive impact on its image and/or reputation through the Social Stock Exchange, and that BOVESPA really gained a better public image. Given the Social Stock Exchange success, BOVESPA now has a better reputation as a sensitive, humanitarian and committed organization with the solution of the social issues these NGOs struggle to mitigate